Coaching across cultures : new tools for leveraging national, corporate, and professional differences - Rosinski, Philippe (London ; Yarmouth, ME : Nicholas Brealey Pub., 2003)
Philippe Rosinski has woven coaching and intercultural communication together into a coherent and accessible whole in Coaching Across Cultures. The book is filled with intriguing examples from multinational companies and includes coaching tools with exercises that put into practice the cultural concepts presented.
Introduction -- PART I: COACHING AND CULTURE: The recent discipline of coaching -- Integrating the cultural dimension -- PART II: LEVERAGING CULTURAL DIFFERENCES: The cultural orientation framework -- How to leverage our sense of power and responsibility -- How to leverage time management approaches -- How to leverage our definitions of identity and purpose - - How to leverage organizational arrangements -- How to leverage our notions of territory and boundaries - - How to leverage communications patterns -- How to leverage modes of thinking -- PART III: FACILITATING THE HIGH-PERFORMANCE AND HIGH- FULFILLMENT JOURNEY: Conduct your assessment -- Articulate objections with the global scorecard -- Progress toward target objectives -- FINAL WORDS: Bringing disciplines, cultures, and people together -- Appendix 1: Transactional analysis -- Appendix 2: Neuro-linguistic programming -- Appendix 3: Soliciting written feedback on your coaching -- Glossary.
Includes bibliographical references (p. [301]-304)
Keywords: Corporate culture; Multiculturalism; Organizational behavior